2020
DOI: 10.21315/mjms2020.27.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ISL1 and LHX5 LIM Homeobox Genes in Bladder Tumourigenesis

Abstract: Introduction: Lin-11, Isl-1 and Mec-3 domains (LIM) homeobox genes are among the most important sub-families of homeobox genes. These genes are thought to play an important role in cancer. In this study, the protein expression of these genes was examined in urothelial carcinoma of the bladder. The expression pattern of Islet-1 (ISL1) and LIM homeobox 5 (LHX5) across different cancer stages and grades, as well as the association between the protein expression of these genes and patient demographics and clinicop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Homeobox genes contain Lin-11, Isl-1, and Mec-3 domains (LIM) subfamilies, which are involved in a series of diseases [ 20 , 32 ], including various types of cancer [ 33 ]. LHX5 , a vital member of the LIM family, has been reported to be involved in the regulation of neuronal differentiation and migration during development of the central nervous system [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homeobox genes contain Lin-11, Isl-1, and Mec-3 domains (LIM) subfamilies, which are involved in a series of diseases [ 20 , 32 ], including various types of cancer [ 33 ]. LHX5 , a vital member of the LIM family, has been reported to be involved in the regulation of neuronal differentiation and migration during development of the central nervous system [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…LHX5 also has the potential to promote nerve precursor cell proliferation, neuronal differentiation, and migration during development of the hippocampus [ 34 ]. Dysregulated LHX5 has also been observed in urothelial carcinoma of the bladder [ 33 ]. TLX1 , a key member of the HOX gene family, was first identified in the T-lineage leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…ISL1 plays an important role in a variety of cellular processes, including cytoskeleton genesis, organogenesis, and tumorigenesis ( Zheng and Zhao, 2007 ), and has been found to be a highly specific marker for pancreatic endocrine tumors and metastases ( Schmitt et al, 2008 ). In addition, it was also significantly associated with aggressive tumor characteristics, tumor recurrence, tumor progression, and disease-specific mortality (DSM) in BLCA and plays an important role in multiple stages of bladder tumorigenesis ( Akhir et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have shown that the homeobox gene family is aberrantly expressed in different tumors, such as bladder, bile duct, endometrial, and breast cancers ( Rao et al, 2002 ). In BLCA, ISL1 and LHX5 play important roles in multiple stages of bladder tumorigenesis ( Akhir et al, 2020 ); ZHX3 promotes migration and invasion in vitro and in vivo ( Deng et al, 2021 ). Therefore, the homeobox gene family plays an important role in the development and progression of BLCA.…”
Section: Introductionmentioning
confidence: 99%
“…The search for a reliable biomarker for the diagnosis and prognosis of glioma is therefore of great urgency. Previous reports have confirmed that the HOX gene family plays a vital regulatory role in the evolution of cancers and is strongly associated with prognosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 94%